2009
DOI: 10.1093/brain/awp258
|View full text |Cite
|
Sign up to set email alerts
|

Clinical features of spinal and bulbar muscular atrophy

Abstract: Spinal and bulbar muscular atrophy is an X-linked motor neuron disease caused by a CAG repeat expansion in the androgen receptor gene. To characterize the natural history and define outcome measures for clinical trials, we assessed the clinical history, laboratory findings and muscle strength and function in 57 patients with genetically confirmed disease. We also administered self-assessment questionnaires for activities of daily living, quality of life and erectile function. We found an average delay of over … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
214
2
9

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 170 publications
(233 citation statements)
references
References 35 publications
8
214
2
9
Order By: Relevance
“…Androgen insensitivity mainly shows gynecomastia, hypogonadism, and reduced fertility (azoospermia, oligospermia) [30,31]. Patients with SBMA usually present muscle weakness in their midforties [32]. However, the age of disease onset correlates inversely with the CAG repeat length, i.e., greater CAG repeat lengths correspond to earlier disease onset [29].…”
Section: Discussionmentioning
confidence: 99%
“…Androgen insensitivity mainly shows gynecomastia, hypogonadism, and reduced fertility (azoospermia, oligospermia) [30,31]. Patients with SBMA usually present muscle weakness in their midforties [32]. However, the age of disease onset correlates inversely with the CAG repeat length, i.e., greater CAG repeat lengths correspond to earlier disease onset [29].…”
Section: Discussionmentioning
confidence: 99%
“…1 Associated neurologic symptoms include muscle cramps, tremor, and varying degrees of sensory loss. 1 Signs of androgen resistance (gynecomastia, erectile dysfunction, and reduced fertility), glucose intolerance, and diabetes mellitus are often present. 1 Recently, Brugada-like ECG abnormalities were also described in patients with SBMA.…”
Section: Oy-stersmentioning
confidence: 99%
“…1 Signs of androgen resistance (gynecomastia, erectile dysfunction, and reduced fertility), glucose intolerance, and diabetes mellitus are often present. 1 Recently, Brugada-like ECG abnormalities were also described in patients with SBMA. 2 SBMA is caused by CAG-polyglutamine repeat expansion within the exon 1 of AR.…”
Section: Oy-stersmentioning
confidence: 99%
See 1 more Smart Citation
“…Cable tensiometer has been used in the number of previous studies to measure isometric strength of both upper limb as well as lower limb musculatures [19][20][21][22]. Previous studies have found the effect of aging on the muscle strength.…”
mentioning
confidence: 99%